ЎҚУВЧИЛАРНИНГ КАСБИЙ ҚИЗИҚИШЛАРИ: МУАММО ВА ЕЧИМЛАР - Нишанова, З.Т.; Алимова, Г.К. (SCIENCE and SOCIETY, 2017)
The article presents the professional orientation games and exercises that can be used by school and boarding school psychologists.
Keywords: profession; interest; progress; training; group; trainer; capability; deviate; professional selection; profession orientation